2014
DOI: 10.3906/sag-1311-88
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral hormone replacement therapy on mean platelet volume in postmenopausal women

Abstract: Background/aim: To examine the effects of hormone replacement therapy (HRT) on mean platelet volume (MPV), lipid profile, and C-reactive protein (CRP) levels in postmenopausal women who have a high risk and incidence of cardiovascular disease. Materials and methods:This study was performed retrospectively. Twenty-seven healthy postmenopausal women received 1 mg estradiol and 2 mg drospirenone orally for 6 months. Twenty-eight healthy postmenopausal women not taking any HRT were admitted to the study as the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…before exercise, which was manifested in increased, compared to the OC(-) group, platelet aggregation in the ADP assay. According to some researchers, increased platelet reactivity in women taking oral contraceptives may be caused by an increase in the percentage of large platelets, resulting from accelerated turnover of platelets [23,24,25]. In the presented study, increased turnover of platelets in women taking OC is shown by, firstly, the increased platelet distribution width (PDW) and a slightly lower number of platelets [in comparison with the OC(-) group], and secondly, by a strong positive correlation between the PDW and platelet volume (MPV) and a negative correlation between MPV and the PLT count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…before exercise, which was manifested in increased, compared to the OC(-) group, platelet aggregation in the ADP assay. According to some researchers, increased platelet reactivity in women taking oral contraceptives may be caused by an increase in the percentage of large platelets, resulting from accelerated turnover of platelets [23,24,25]. In the presented study, increased turnover of platelets in women taking OC is shown by, firstly, the increased platelet distribution width (PDW) and a slightly lower number of platelets [in comparison with the OC(-) group], and secondly, by a strong positive correlation between the PDW and platelet volume (MPV) and a negative correlation between MPV and the PLT count.…”
Section: Discussionmentioning
confidence: 99%
“…Among other potential mechanisms of the thrombotic action of hormonal contraceptives, the intensity of the myeloid trombocytopoesis and increased platelet reactivity should be considered. The increase in platelet reactivity under the influence of estradiol is perhaps a consequence of an increase in the percentage of large platelets, which is also reflected in an increase in platelet volume (MPV) [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что PAI-1 является маркером субклинического воспаления и, наряду с С-реактивным белком и IL-6, ассоциируется с инсулинорезистентностью и гипертензией [16]. Приведенные данные, наряду с результатами аналогичных исследований [17,18], могут свидетельствовать в пользу снижения риска сердечно-сосудистых заболеваний у женщин с МС в постменопаузе на фоне приема 17β-эстрадиол/дроспиренон.…”
Section: таблица эффективность терапии климактерического синдрома коunclassified
“…Studies have indicated that estrogen can regulate lipid homeostasis in the adipose tissue, liver and brain, as well as prevent metabolic dyslipidemia [13]. Furthermore, clinical evidence demonstrates that estrogen replacement therapy can reduce the risk of cardiovascular disease in postmenopausal women by improving lipid metabolism [14, 15]. Further studies are needed to identify the mechanisms by which estrogen regulates lipid metabolism and delays the development of cardiovascular disease in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%